2004
DOI: 10.32635/2176-9745.rbc.2004v50n3.2022
|View full text |Cite
|
Sign up to set email alerts
|

Freqüência de imunofenótipos aberrantes em leucemias agudas

Abstract: As leucemias agudas (LA) são doenças heterogêneas, com características clínicas, morfológicas, imunológicas e moleculares distintas. Por meio destas particularidades, as leucemias são classificadas em seus diversos subtipos biológicos. Neste estudo, nós analisamos a freqüência de fenótipos aberrantes (FA) em pacientes com leucemias, provenientes de diferentes regiões do Brasil, com o objetivo de avaliar estes FAs nos estudos futuros sobre doença residual mínima. Análises por citometria de fluxo multiparamétric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The present study demonstrated a higher frequency of CD7 than other investigations, ranging from 8.8% to 33%. (16,27) CD7 expression in myeloblasts has been associated with failure to achieve complete remission and decreased survival. (28,29) It is believed that CD7 is expressed in early stages of hematopoietic ontogeny and has been associated with expression of precursor antigens.…”
Section: ❚ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study demonstrated a higher frequency of CD7 than other investigations, ranging from 8.8% to 33%. (16,27) CD7 expression in myeloblasts has been associated with failure to achieve complete remission and decreased survival. (28,29) It is believed that CD7 is expressed in early stages of hematopoietic ontogeny and has been associated with expression of precursor antigens.…”
Section: ❚ Discussionmentioning
confidence: 99%
“…In addition, aberrant immunophenotypes are known to be relevant tools to detect minimal residual disease. (14,16,17) Demographic characteristics, such as age, sex and race, have been used to evaluate the risk of leukemia. Individuals aged 1 to 10 years have a favorable prognosis, while the age groups <1 year and >10 years have an adverse prognosis.…”
Section: ❚ Introductionmentioning
confidence: 99%